A mid-term follow-up retrospective evaluation of tarsometatarsal joint fracture-dislocations treated by closed reduction and percutaneous K-wires fixation. Issue 6 (June 2021) - Mosca, Massimiliano; Fuiano, Mario; Censoni, Davide; Marcheggiani Muccioli, Giulio Maria; Roberti di Sarsina, Tommaso; Grassi, Alberto; Caravelli, Silvio; Zaffagnini, Stefano
Highlights: The purpose of this study is to determine the efficacy of the treatment of Lisfranc injuries by closed reduction and percutaneous fixation with K-wires. More than 2 year of follow up. The results showed optimal clinical outcome, no loss of reduction at follow up and a low rate of complications. Abstract: Introduction: Injuries involving the tarsometatarsal (TMT) joint are relatively uncommon, and the surgical treatment is potentially characterized by a high complications rate. The purpose of this study is to evaluate the results of the treatment of Lisfranc fracture-dislocations treated with closed reduction and percutaneous fixation with K-wires, considering complications and re-intervantion rate. Materials and methods: A retrospective review was performed on all patients undergone closed reduction and percutaneous fixation with K-wires of a Lisfranc fracture-dislocation. Patients have been clinically evaluated at last follow up by American Orthopaedic Foot and Ankle Society (AOFAS) midfoot score and Visual Analogue Scale (VAS), as well as by radiograph assessment. Results: Following inclusion and exclusion criteria, 15 patients have been included, with a mean age of 48.2 ± 5.6 years. Average follow-up was 3.8 ± 1.8 years (range 1–6). 7 fractures analyzed were classified as type A, 7 as type B (3 were B1, 4 were B2) and 1 as type C1. No case of loss of reduction has been observed at radiographic 1-month follow-up. At last follow-up mean AOFAS midfoot score and VAS score were respectively 82.2 ± 10.4 and 1.5 ± 1.3. Registered complications showed one deep vein thrombosis and 2 cases of complex regional pain syndrome (CRPS). One patient subsequently underwent arthrodesis of the tarsometatarsal joint for post-traumatic arthritis. Conclusions: The treatment of the fracture-dislocations of the Lisfranc joint by percutaneous reduction and fixation with K-wire can achieve good clinical outcomes with a low rate of complications and reoperations. Level of Evidence: Level IV